Biomarkers of Transplantation Tolerance: More Hopeful than Helpful? - Cobbold, Stephen P.; Adams, Alizabeth; Waldmann, Herman (Frontiers in Immunology, 2011)
A major limitation to the translation of tolerogenic therapies to clinical transplantation is a lack of biomarkers that can be used as surrogate measures for predicting the successful induction of immune tolerance which would allow for the safe withdrawal of immunosuppression. We have used 3 different mouse models of donor specific tolerance to skin grafts together with quantitative RT-PCR to search for potential biomarkers of tolerance using criteria based on the presence or activity of regulatory T cells and antigen presenting cells within grafts or lymphoid organs. We find that significant differences in gene expression between tolerated and rejecting grafts are observed primarily within the grafted skin and not systemically or in the draining lymph node. The pattern of gene expression within long-term surviving tolerated grafts appear very similar to syngeneic grafts, with both having low levels of T cell and APC infiltration and a bias towards relative over-expression of “regulatory-associated” genes, while allografts destined for rejection show an overall increase in both “regulatory” and “effector” cell associated transcripts. We also, however, find an increase in a large number of regulatory genes, of both innate and T cell origin, even after grafting syngeneic skin. Taken together, these findings suggest that there may be no tissue biomarkers uniquely able to predict donor antigen specific tolerance per se, but that patterns of gene expression within tolerated grafts may be similar to those found in self tissues recovering from an inflammatory insult.